FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - SILVIA ANGGRENI; MUNGNIYATI MUNGNIYATI (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study is to examine the factors that influence firm value. The independent variables are managerial ownership, institusional ownership, capital structure, profitability, profit growth, firm size, leverage. The dependent variable is firm value measured by price book value.The object are manufacture companies listed in Indonesia Stock Exchange (IDX) from the period of 2014 to 2016. This study used 66 samples and samples selection procedure used purposive sampling. Data were analyzed using multiple regression method. The result of this study indicate that profitability, profit growth, firm size has influence toward price book value. Other variables such as managerial ownership, institusional ownership, capital structure, leverage have no influence toward price book value